2011
DOI: 10.3109/09638288.2011.607218
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different interventions using a psychosocial subgroup assignment in chronic neck and back pain patients: a 10-year follow-up

Abstract: In terms of long-term follow-up of sickness absence, the multidisciplinary programme appears to be most beneficial for DYS and AC patients. In contrast, the CBT and PT interventions failed to benefit any patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
1
46
0
2
Order By: Relevance
“…This group was originally considered to have random or exaggerated responses on scales, and Rudy recognized that some valid but unusual profiles might be misclassified as Anomalous. 28 Consistent with a previous study demonstrating higher psychosocial functioning in those with an Anomalous profile, 21 this group was indeed shown to be functioning at a higher level than even the typical AC patient in the present study. Furthermore, most of Anomalous patients at FRP discharge were associated with better socioeconomic outcomes at 1 year, including a higher work retention rate, lower health care utilization, and no surgery to the original injury site.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This group was originally considered to have random or exaggerated responses on scales, and Rudy recognized that some valid but unusual profiles might be misclassified as Anomalous. 28 Consistent with a previous study demonstrating higher psychosocial functioning in those with an Anomalous profile, 21 this group was indeed shown to be functioning at a higher level than even the typical AC patient in the present study. Furthermore, most of Anomalous patients at FRP discharge were associated with better socioeconomic outcomes at 1 year, including a higher work retention rate, lower health care utilization, and no surgery to the original injury site.…”
Section: Discussionsupporting
confidence: 93%
“…27 The 3 main MPI profiles are: Adaptive Coper (AC), characterized as having low levels of pain and distress, few functional limitations, and a high sense of life control; Interpersonally Distressed (ID), characterized by a lack of social support; and Dysfunctional (DYS), characterized by severe pain, affective distress, significant impairment of daily living skills, and a perceived lack of control. These classifications are associated with other painrelated functional measures, such as pain severity, disability, work productivity, [28][29][30] and quality of life. 31 Recent evidence shows that the 3 MPI groups were successfully identified, and were associated with different levels of pain severity, perceived disability, and depression in CDOMD patients.…”
mentioning
confidence: 99%
“…Also, a few studies reported no differences between the CBT and control groups, or marginal effects that were not maintained at follow-up 4851…”
Section: Resultsmentioning
confidence: 99%
“…In line with this notion, a study showed that a type of cognitive behavioral approach, termed graded exposure in vivo treatment, aiming at restoration of function, activities of daily living, and return to work rather than reducing pain, was useful in reducing pain-related fear in patients with work-related upper extremity pain in general and not specifically in those with cervical radiculopathy (16). Additionally, two recent randomized controlled trials (Jadad scores: 4 and 5) provided some evidence of effectiveness of cognitive behavioral treatments combined with a physical therapy program consisting of mostly exercises in terms of long-term sickness absence and pain, disability, and quality of life in combined groups of neck pain patients with no exclusion criteria for radicular findings (17,18).…”
Section: Educational Interventionsmentioning
confidence: 99%